Artificial intelligence paradigms for smart cyber-physical systems - Luhach, Ashish Kumar; Elçi, Atilla (IGI Global, Publisher of Timely Knowledge, 2021)
"This book focuses upon the recent advances in the realization of Artificial Intelligence-based approaches towards affecting secure Cyber-Physical Systems. It features contributions pertaining to this multidisciplinary paradigm, in particular, in its application to building sustainable space by investigating state-of-art research issues, applications and achievements in the field of Computational Intelligence Paradigms for Cyber-Physical Systems" - Provided by publisher
Keywords: Computer networks / Security measures / Data processing; Internet of things / Security measures / Data processing; Cooperating objects (Computer systems); Artificial intelligence / Industrial applications